Financial Distress, Transfer Pricing, and Inventory Intensity: Their Effects on Tax Avoidance in Mining Companies - Akbar, Muhammad Fahrial; Listya, Anisa; Patmawati (Journal of Applied Accounting and Taxation, 2025)
This research aims to examine the effect of financial distress, transfer pricing, and inventory intensity on tax avoidance in mining companies listed on the Indonesia Stock Exchange for the 2020–2023 period. The research sample consists of 84 companies selected using the purposive sampling method with secondary data obtained from the IDX and the official websites of the respective companies. Data analysis was conducted using multiple linear regression with SPSS version 27. The results show that financial distress and transfer pricing have no effect on tax avoidance due to strict government oversight and the high risk of being audited, while inventory intensity affects tax avoidance because inventory related costs can reduce taxable income.